2021
DOI: 10.1111/ijfs.15255
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of volatile compounds during dry‐cured deer loin processing

Abstract: During dry-cured meat processing, several reactions leads to the development of volatile organic compounds (VOCs) responsible for a typical flavour and aroma. Hence, this study aimed to access the evolution of VOCs profile in dry-cured deer loin during its manufacture at day 0, 30 and 60. For the sake of characterising the changes of VOCs, 8 chemical families (95 compounds) were identified, with the hydrocarbons (terpenes), ketones, acids and aldehydes as the most powerful descriptors for ripening period. Mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The use of game meat is particularly important in the production of high-quality meat products such as dry-cured meat products. The study by Vargas-Ramella et al (2021) on the chemical and physical-chemical changes during the dry-cured processing of deer loin confirmed that deer meat is an excellent candidate for the production of dry-cured loin.…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…The use of game meat is particularly important in the production of high-quality meat products such as dry-cured meat products. The study by Vargas-Ramella et al (2021) on the chemical and physical-chemical changes during the dry-cured processing of deer loin confirmed that deer meat is an excellent candidate for the production of dry-cured loin.…”
mentioning
confidence: 65%
“…The study by Vargas‐Ramella et al . (2021) on the chemical and physical–chemical changes during the dry‐cured processing of deer loin confirmed that deer meat is an excellent candidate for the production of dry‐cured loin.…”
mentioning
confidence: 83%
See 1 more Smart Citation